1974
DOI: 10.1104/pp.53.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of Nonwoody Plant Tissues

Abstract: Small cylinders of red beet (Beta vulgaris) root were frozen at various rates. Ultraslow cooling at 0.2 C per hour to -4 C produced little damage, as determined by leakage of pigment and electrolytes, and softening. All of these increased at faster rates of cooling or at lower temperatures. Cooling at the ultraslow rate appears to induce extracellular freezing, resulting in a protective dehydration of the cell contents.with the requirements of large pieces of tissue, encourage the formation of extracellular ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Rottenburg Interpretation of FR-1 and FR-2 as representing the freezing of extracellular and cellular liquids, respectively, may provide an explanation of the cell-protective effect of ultraslow cooling, as reported in the preceding paper (4). The gross transfer of water out of the cell shown by Figure 3 of that paper (4) presumably concentrated the cellular contents and lowered its freezing temperature (FR-2) so that the cells no longer froze at the -4 C terminal temperature of those experiments. It would also follow from this interpretation that at just a few degrees below -4 C, a damaging degree of freezing would be expected, even under conditions of ultraslow cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rottenburg Interpretation of FR-1 and FR-2 as representing the freezing of extracellular and cellular liquids, respectively, may provide an explanation of the cell-protective effect of ultraslow cooling, as reported in the preceding paper (4). The gross transfer of water out of the cell shown by Figure 3 of that paper (4) presumably concentrated the cellular contents and lowered its freezing temperature (FR-2) so that the cells no longer froze at the -4 C terminal temperature of those experiments. It would also follow from this interpretation that at just a few degrees below -4 C, a damaging degree of freezing would be expected, even under conditions of ultraslow cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature at the center was measured with a thermistor mounted in a 24-gauge hypodermic needle and recorded as described previously (4). Tissues studied included primarily the parenchyma of cucumber (Cucumis sativus), peach (Prunus persica) and cantaloupe (Cucumis melo cantalupensis).…”
Section: Methodsmentioning
confidence: 99%
“…There are two classes of cryoprotectants viz. penetrating and non-penetrating (Finkle et al, 1985;Benson, 2008a). Penetrating cryoprotectants can move across cell membranes and in so doing, prevent ice crystal formation and membrane rupture during freezing (Wolfe et al, 2002;de Lara Janz et al, 2012).…”
Section: Cryoprotectionmentioning
confidence: 99%
“…Despite their ability to enhance vitrification, scavenge ROS and enhance tissue survival after cooling, cryoprotectants can also be cytotoxic to plant tissues (Kistnasamy et al, 2011;Best, 2015). Cell death may occur as a result of intracellular solute accumulation and/or plasma membrane collapse due to changes in osmotic pressure associated with the dehydrating properties of cryoprotectants (Finkle et al, 1985). In an attempt to cryopreserve explants from E. capensis, Hajari et al (2011) reported improved survival after the explants were cryoprotected with a combination of penetrating cryoprotectants (DMSO and glycerol).…”
Section: Cryoprotectionmentioning
confidence: 99%